Evidence of ethnic discrimination in the Swedish labor market using experimental data - Magnus Carlsson; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2006)
We present experimental evidence for recruitment discrimination against men with an Arabic sounding name. Our results show that every fourth employer discriminates against the minority. However, simulations indicate that ethnic discrimination is only responsible for less than one sixth of the native-immigrant unemployment gap. We extend previous analyses using this method by interviewing employers. We find that discriminatory employers have, to a greater extent, a male responsible for recruitment and a share of male employees greater than 35 percent. Firms that have an ethnic multitude plan were not found to discriminate less than other firms.
Keywords: 330; Ethnische Diskriminierung; Arbeitsmarktdiskriminierung; Schweden